STUDI PENGAPLIKASIAN EFEK FOTOKATALIS DARI LAPISAN ZnO:Ag TERHADAP DEGRADASI BAKTERI E.coli - Ndaru Adyono; Heri Sutanto; Iis Nurhasanah (Youngster Physics Journal, 2015)
Research in the field of green technology using photocatalyst materials can be a solution to environmental pollution, especially contamination of aquatic bacteria. These materials absorb energy from the sun and form hydroxyl radicals that kill bacteria. Zinc oxide has a high photocatalytic efficiency with Eg 3.3 eV in the range of UV - visible light. ZnO can be modified by addition of silver in order to improve the effectiveness as well as anti-bacterial properties. ZnO:Ag 4% layers prepared with thermal spray coating method with deposition temperature at 250ºC and aneling temperature at 450 ºC. XRD measurements performed with CuKα radiation with wavelength at 1.54060 Å and the diffraction angle in range 20 ° - 70 °. The diffraction patterns were identified using the Crystallography Open Database (COD) and software QUALX. ZnO (Id 101-1259) phase and metal Ag (Id 151-2487) phase has formed, but there are also silver oxide phase AgO (Id 150-9488) and Ag2O (Id 150-9684). Crystallite size has been calculated using Debye-Scherrer equation resulted an average value 43.46 nm. The optical properties were measured using a UV-Vis spectrometer in the wavelength range 250-800 nm. Transmittance spectrum were converted into an absorbance spectrum using the Beer-Lambert law. Eg value were analyzed with methods tauc's plot. Linear extrapolation (αhν)2 against hν provide direct transition Eg value 3.1 eV. Photodegradation ability of ZnO:Ag layer performed on E.coli bacteria. TPC measurement results were analyzed using the degradation rate graph, Ct (bacteria concentration) against time exposure. The degradation rate values obtained 1.554 x 10-17 (cfu/ml)-2(minutes)-1.Keywords : ZnO:Ag, band gap energy, XRD, Uv-Vis, TPC, degradation rate.